On a Topological Space Generated by Monophonic Eccentric Neighborhoods of a Graph (European Journal of Pure and Applied Mathematics, 2021)
In this paper, we present a way of constructing a topology on a vertex set of a graph using monophonic eccentric neighborhoods of the graph G.Â In this type of construction, we characterize those graphs that induced the indiscrete topology, the discrete topology, and a particular point topology.